Penerapan Penerimaan Negara Bukan Pajak (PNBP) Atas Bea Lelang Pada Kantor Pelayanan Kekayaan Negara Dan Lelang (KPKNL) XXX - Misya Arla Ratia; Sartika, Novira (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2024)
This study aims to determine Non-Tax State Revenue (PNBP) at the XXX State Wealth and Auction Service Office (KPKNL) for a period of 3 (three) years, from 2020 to 2022, and the administration of Non-Tax State Revenue (PNBP) derived from Auction Fees at the XXX State Wealth and Auction Service Office (KPKNL). This research is descriptive research with a qualitative approach and a quantitative approach. This research data was obtained from the XXX State Wealth and Auction Service Office (KPKNL). The data collection techniques used were interviews and documentation. The results showed that the development of PNBP on Auction Duty carried out by the KPKNL in increasing auction duties was optimally carried out. Even though in 2021 the revenue for the auction duty target did not reach realization, in 2022 KPKNL XXX had reached the realization of the set target, and the auction was in the highest selling status. In administering the auction money, KPKNL has carried out procedures in accordance with the legal basis used, namely the Regulation of the Minister of Finance of the Republic of Indonesia Number 213/PMK.06/2020 concerning Guidelines for the Implementation of Auctions and further regulates the administration carried out by KPKNL in the Regulation of the Director General of State Assets Number 2/KN/2022 concerning Guidelines for Auction Administration at the State Wealth and Auction Service Office. Keywords : Application, Non-Tax State Revenue (PNBP), Administration, Auction Duty